2014
DOI: 10.1099/mic.0.082677-0
|View full text |Cite
|
Sign up to set email alerts
|

darR and darS are regulatory genes that modulate 2-hexyl, 5-propyl resorcinol transcription in Pseudomonas chlororaphis PCL1606

Abstract: Pseudomonas chlororaphis PCL1606 synthesizes the antifungal antibiotic 2-hexyl, 5-propyl resorcinol (HPR), which is crucial for the biocontrol of fungal soil-borne pathogens. The genetic basis for HPR production lies in the dar genes, which are directly involved in the biosynthesis of HPR. In the present study, we elucidated the genetic features of the dar genes. Reverse transcription PCR experiments revealed an independent organization of the dar genes, except for darBC, which was transcribed as a polycistron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 43 publications
4
8
0
Order By: Relevance
“…A comprehensive search in the databases revealed that diverse proteins showed remarkable similarities to this conserved domain at short regions. A number of regulator proteins can be found among these hits, i.e., a short fragment of the MarR family transcriptional regulator of Pseudomonas chlororaphis or a similar fragment of the DNA-binding transcription factor ADR1 of Saccharomyces cerevisiae (31,32). Additionally, similarities of this region were shown to the DNAdirected RNA polymerase sigma-70 factor of Pseudoalteromonas undina and to ABC transporter permeases of various bacteria among a large number of hits for hypothetical proteins of various organisms.…”
Section: Resultsmentioning
confidence: 99%
“…A comprehensive search in the databases revealed that diverse proteins showed remarkable similarities to this conserved domain at short regions. A number of regulator proteins can be found among these hits, i.e., a short fragment of the MarR family transcriptional regulator of Pseudomonas chlororaphis or a similar fragment of the DNA-binding transcription factor ADR1 of Saccharomyces cerevisiae (31,32). Additionally, similarities of this region were shown to the DNAdirected RNA polymerase sigma-70 factor of Pseudoalteromonas undina and to ABC transporter permeases of various bacteria among a large number of hits for hypothetical proteins of various organisms.…”
Section: Resultsmentioning
confidence: 99%
“…The wild-type strain PcPCL1606 was used as a reference for antibiotic production (Cazorla et al, 2006). The HPR production was quantified as previously described (Calderón et al, 2014a).…”
Section: Methodsmentioning
confidence: 99%
“…For chemical complementation assays, PcPCL1606 cultures were grown in a 200 mL TPG medium for 28 h at 25°C under orbital shaking (150 rpm), and the production and accumulation of HPR were confirmed as previously described (Calderón et al, 2014a). The cultures were centrifuged, sterilized by filtration (0.22-μm filter), and the cell-free supernatant was collected.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations